ปัจจัยที่มีอิทธิพลต่อประเภทของนักท่องเที่ยวชาวญี่ปุ่นในจังหวัดเชียงใหม่ - ธนวัต คองประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This study aims to investigate factors influencing types of Japanese tourists and Japanese tourist’s travel behavior in Chiang Mai, which can be classified as short-stay tourists (Staying in Chiang Mai less than 30 days) and long-stay tourists (Staying in Chiang Mai at least 30 days). There are 3 factors to be examined in this study which are 1.Demographic factors consisting of ‘Gender’, ‘Age’, ‘Marital status’, ‘Education’, ‘Career’ and ‘Income’ 2. Push factors consisting of ‘Novelty Seeking’, ‘Relaxation/Escape’, ‘Adventure/Thrills/Entertainment’ ‘Intellectual/Cultural Enrichment’ and ‘Self-fulfillment/Actualization’ and 3. Pull Factors consisting of ‘Tourism Resources’, ‘Geography of Chiang Mai/Location’, ‘Facilities’, ‘Local People/Cultures/Traditions/Festivals’, ‘Accommodations’, ‘Cost of Living/Expenses’ and ‘Governmental and Public Policy regarding tourism in Thailand’.The data has been gathered from 480 questionnaires of which 400 are from short-stay tourists and 80 are from long-stay tourists. The statistic tools used are Frequency, Percentage, Mean, Standard Deviation and Logistic Regression Analysis in order to analyze the relationship between each factor (From demographic factors, push factors and pull factors) and types of Japanese tourists in Chiang Mai.According to the research result, factors influencing types of Japanese tourists in Chiang Mai are income in the level of more than 90,001 Baht a month (Demographic factors), the Novelty Seeking and Self-fulfillment/Actualization (Push factors), the Geography of Chiang Mai or location , Facilities , Local people/cultures/traditions/ festivals , Accommodations , and Cost of living/expenses (Pull factors). It is also found that ‘Facilities’ is influencing types of Japanese tourists the most.The suggestions derived from this research is that government sector and travel related organizations should continuously promote Thailand to be the top travel destination among Japanese through various channels of media advertising such as magazine, internet, exhibition, etc. suitable for each type of traveller. And to promote Chiang Mai to be the destination for Japanese long-stay travellers, facilities which are transportation, Thai food, wellness and medical center should be the main priority to be focused. Moreover law and regulation should accommodate and motivate Japanese traveller to travel and stay in Thai longer in a more convenient way.